Prejuízos metabólicos e comportamentais tardios decorrentes de exposição intrauterina e neonatal à diabetes mellitus gestacional - SOUSA, Nayra Oliveira (2024)
Diabetes mellitus is a condition with various causes, characterized by high blood sugar levels and disruptions in the metabolism of carbohydrates, fats, and proteins. These changes affect both the metabolism and structure of different tissues in the body. When this condition occurs during pregnancy, it's called gestational diabetes (GD), which is the most common complication during pregnancy. GD involves intolerance to glucose during pregnancy and not only poses risks to the pregnant woman but also creates an unfavorable environment for the developing fetus. This environment can predispose the fetus to developing chronic diseases later in life, such as non-alcoholic fatty liver disease (NAFLD) and neurodegenerative disorders. However, the exact metabolic and neurological changes caused by GD are not fully understood, and there's a lack of research on the long-term effects of GD compared to Type 2 Diabetes mellitus. This study aimed to investigate the development of metabolic and behavioral issues in adult rats exposed to GD during the intrauterine and neonatal periods. Initially, 16 pairs of Wistar rats were mated, and after confirming pregnancy on the 13th day, the rats were divided into two groups for GD induction: a control group, where rats received only saline solution, and a ges- tational diabetes group, where rats received a dose of streptozotocin (STZ) to induce GD. After weaning, the offspring were further divided into three groups: a control group with standard nutrition, a group induced with type 2 diabetes (T2DM) through a sucrose solution, and a group with offspring of rats that received STZ during pregnancy (DG). Various parameters were eval- uated in the rats, including body measurements, blood sugar and lipid levels, insulin resistance, liver function, and behavioral traits such as anxiety and cognitive abilities. The results showed that mothers developed GD with significant weight loss, severe hyperglycemia, and insulin resistance. The offspring of the GD group showed reduced birth rates, weight, and neonatal hyperglycemia. In adulthood, the DG group exhibited several chronic conditions including di- abetes, NAFLD, and behavioral issues like anxiety and cognitive deficits. The T2DM group, on the other hand, developed obesity and more severe metabolic changes compared to the GD group but showed milder NAFLD. These findings demonstrate that adverse conditions during gestation and early life, such as GD, can significantly impact the future development of meta- bolic disorders and neurological issues, even if the individual maintains a healthy diet after weaning.